Scienze umane e verità dei saperi - Sini, Carlo (Laboratorio dell'ISPF, 2015)
Humanities and the truth of knowledge]. A reflection about the crushing of the notion of culture in contemporary age and about the paradoxes and problems arising from the present trend to impose heteronomous values to the research. Without a proper use of the gaze of history, of the work of philosophy, of the investigation into the hidden ethical and political sense of the intellectual activity, all our knowledge – both scientific natural and humanistic – is doomed to be deprived of self-awareness: i.e. either prey of a fetishistic naturalism or, on the other hand, of a rhetorical and abstract idealism.